2008
DOI: 10.1253/circj.cj-07-0712
|View full text |Cite
|
Sign up to set email alerts
|

Primary Percutaneous Coronary Intervention vs Conservative Treatment for Acute ST Elevation Myocardial Infarction Short- and Long-Term Follow-up According to Disease Severity

Abstract: n recent years, primary percutaneous coronary intervention (PPCI) has gradually emerged as the preferred treatment strategy for ST-elevation myocardial infarction (STEMI). 1,2 In particular, the usefulness of PPCI for acute myocardial infarction (AMI) resulting in cardiogenic shock has been recognised. 3 In the treatment of STEMI, PPCI is associated with favourable vital prognosis, 4 and current therapeutic guidelines for STEMI recommend PPCI whenever feasible. 5,6 Numerous randomized studies and meta-analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…A recent pooled meta-analysis confirmed that absolute risk reduction for mortality using thrombolytics or primary PCI depended on the patient’s baseline risk [17]. Other studies have shown that in low risk patients, fibrinolysis [18] and even conservative therapy [19] performed as well as primary PCI for 30-day mortality. Therefore, the use of the TIMI risk score in Malaysia may help improve the use of limited resources through better targeted treatment for higher risk patients.…”
Section: Discussionmentioning
confidence: 93%
“…A recent pooled meta-analysis confirmed that absolute risk reduction for mortality using thrombolytics or primary PCI depended on the patient’s baseline risk [17]. Other studies have shown that in low risk patients, fibrinolysis [18] and even conservative therapy [19] performed as well as primary PCI for 30-day mortality. Therefore, the use of the TIMI risk score in Malaysia may help improve the use of limited resources through better targeted treatment for higher risk patients.…”
Section: Discussionmentioning
confidence: 93%
“…European randomized trials also support transferring patients from community hospitals to tertiary PCI centers for primary PCI. 23, 24 From a clinical perspective, 1 recent study reported that low-risk patients may not benefit from primary PCI, 25 suggesting that this therapy may not be indicated for all patients. The recent registry study also revealed an increased number of elderly patients with AMI 13 and suggested appropriate treatment for such patients.…”
Section: Discussionmentioning
confidence: 99%